2017
DOI: 10.1002/cphc.201700111
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of T‐ and H‐Phase Two‐Dimensional Transition‐Metal Carbides/Nitrides and Their Semiconducting–Metallic Phase Transition

Abstract: The discovery of various two-dimensional (2D) nanomaterials with different phases is fundamentally and technologically intriguing, leading to diverse physical and chemical properties for expanded applications. Herein, we performed systematic first-principles calculations to explore a series of single-layer MXenes (M X: M=Sc, Ti, V, Cr, Mn, Zr, Nb, Mo, Hf, Ta; X=C, N). The new H-phase MXenes are firstly predicted, which are compared with the usually synthesized MXenes named as T-phase MXenes on their structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…2×2×1 supercell of Ti 2 CO 2 is selected as a study model, denoted as Ti 8 C 4 O 8 , contains four upper O and four lower O atoms, as shown in Figure a. The terminal O group located in the hollow sites of Ti 8 C 4 on both sites has been reported as the most thermally stable structure ,. Δ G H has been found to be dependent upon hydrogen coverages in Ti 2 CO 2 , which presented Δ G H =0.12 eV at low hydrogen coverage (1/9 ML) and larger values with increasing hydrogen coverages .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2×2×1 supercell of Ti 2 CO 2 is selected as a study model, denoted as Ti 8 C 4 O 8 , contains four upper O and four lower O atoms, as shown in Figure a. The terminal O group located in the hollow sites of Ti 8 C 4 on both sites has been reported as the most thermally stable structure ,. Δ G H has been found to be dependent upon hydrogen coverages in Ti 2 CO 2 , which presented Δ G H =0.12 eV at low hydrogen coverage (1/9 ML) and larger values with increasing hydrogen coverages .…”
Section: Resultsmentioning
confidence: 99%
“…where E totol , E vac and E bulk correspond to the total energies of the doping system, vacancy and P/S bulk, and n is the number of atoms in P/S bulk. [47] In addition, the dynamical stability of the catalysts is also explored by using temperature molecular dynamics (MD), [48] which are performed in the NVT ensemble for 5000 time-steps. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 within 50 K and the structures are remaining unchanged, as displayed in Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…In the following subsections, we discuss the obtained 1T/1H (TMDCs and TMDOs, metal dihalides, MXenes/BiXenes, and other 1T/1H), planar and distorted planar structures, memory structures, and other characteristic structures in detail. Experimental data reported by J. Zhou et al 48 and other groups 88,[90][91][92][93][94][95]111 are shown in Table 1 and shown in Fig. 7, T 0 indicates the one-dimensional distorted 1T phase in which pairs of metal atoms move closer to each other perpendicularly, and 1T 00 indicates the two-dimensional distorted 1T phase in which four nearby metal atoms move closer to each other.…”
Section: Space-group Classificationmentioning
confidence: 97%
“…This work focuses on the magnetism of pristine MXenes, whose geometric structures are similar to transition metal chalcogenides in two common phases (1H and 1T). 36,37 Theoretical exploration via rst-principles calculations was conducted on the stability, magnetism, and electronic properties of the 1H and 1T M 2 C MXenes with various transition metals (M ¼ Sc, Ti, Fe, Co, Ni, Cu, Zn). The corresponding parameters, including the lattice parameters, total energies, magnetic moments, and spin exchange coupling parameters, were calculated and compared, and the critical temperatures T c for particular magnetic MXenes were evaluated through Monte Carlo (MC) simulations.…”
Section: Introductionmentioning
confidence: 99%